'It Just Had to Settle': A Longitudinal Investigation of Students' Developmental Readiness to Navigate Dissonance and Experience Transformation Through International Service Learning. (4th March 2018) - Taylor, Kari B.; Jones, Susan; Massey, Rachel; Mickey, Jasmine; Reynolds, Danyelle J.
ABSTRACT: The purpose of this longitudinal study was to investigate students' developmental readiness to navigate dissonance and experience transformation as they engaged in an international service-learning program. Using case-study methodology, researchers collected data from a diverse group of 7 graduate students and 5 undergraduate students who participated in a predeparture course and 3-week program in Ecuador. Data were collected at 4 points in time: before the trip, during the trip, immediately after participants' return to the United States, and 1 year later. The findings emphasize 2 main narratives that describe the longitudinal nature of participants' developmental readiness. These 2 narratives include remaining unsure how to do "good service" and reexamining what social identities mean. Collectively, the longitudinal narratives demonstrate that participants continued to consider and, in some cases, made new meaning of experiences in Ecuador that sparked dissonance; however, the transformative potential of international service learning took time to materialize.